2017
DOI: 10.28920/dhm47.4.216-222
|View full text |Cite
|
Sign up to set email alerts
|

Influence of repetitive diving in saltwater on pressure equalization and Eustachian tube function in recreational scuba divers

Abstract: To promote and facilitate the study of all aspects of underwater and hyperbaric medicine To provide information on underwater and hyperbaric medicine To publish a journal and to convene members of each Society annually at a scientific conference OFFICE HOLDERS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…This symptom mainly aff ected people with allergic rhinitis or acute rhinitis [15]. In contrast, Jansen et al showed signifi cantly higher middle ear peak pressures and higher pressure diff erences after equilibration maneuvers in people with exposure of the Eustachian tube to increased atmospheric pressure [6,13]. Therefore, any patient who reports the symptom of a "plugged ear" should have a tympanometry test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This symptom mainly aff ected people with allergic rhinitis or acute rhinitis [15]. In contrast, Jansen et al showed signifi cantly higher middle ear peak pressures and higher pressure diff erences after equilibration maneuvers in people with exposure of the Eustachian tube to increased atmospheric pressure [6,13]. Therefore, any patient who reports the symptom of a "plugged ear" should have a tympanometry test.…”
Section: Discussionmentioning
confidence: 99%
“…Patients operated on for hypertrophic lesions of the inferior nasal turbinates usually report from the fi rst day, apart from pain, obstruction of the nasal cavity and a feeling of "plugged ears" [7,9,10,13]. Pain most often subsides after a few hours, nasal obstruction usually resolves between 5 and 7 days after surgery, while the feeling of "plugged ears" can persist much longer [5,8,10,21,23,29].…”
Section: Introductionmentioning
confidence: 99%
“…ETOD defines the time span between opening and closing of the ET. Evaluation of the ET parameters in detail are demonstrated in previously published articles [8,9,12,13].…”
Section: Eustachian Tube Function Parametermentioning
confidence: 99%